Philosophy and Language in the Islamic World. Vol. 2 - Adamson, Peter; Germann, Nadja; Hajatpour, Reza; Rudolph, Ulrich; Tamer, Goerges (Philosophy in the Islamic World in Context, 2021)
Audience: All those intererested in philosophy of language, Islamic intellectual history, linguistics, theology, philosophy.
Keywords: kielifilosofia; semantiikka; pragmatiikka; islam; Philosophy of language; Semantics; Pragmatics; Islam